An Extract Produced by Bacillus sp. BR3 Influences the Function of the GacS/GacA Two-Component System in Pseudomonas syringae pv. tomato DC3000 - Zhang, Bo; Zhang, Yang; Liang, Fei; Ma, Yinan; Wu, Xiaogang (Frontiers in Microbiology, 2019)
The GacS/GacA two-component system is essential for virulence in many plant pathogenic bacteria, and thus represents a promising anti-virulence target. In the present study, we isolated and screened rhizobacteria that were capable of inhibiting the expression of the gacS gene in the phytopathogenic bacterium Pseudomonas syringae pv. tomato (Pto) DC3000. One candidate inhibitor bacterium, BR3 was obtained and identified as a Bacillus sp. strain based on 16s rRNA gene sequence analysis. Besides the gacS gene, the GacA-dependent small RNA genes rsmZ and rsmY were repressed transcriptionally when DC3000 was treated with an extract from strain BR3. Importantly, the extract also influenced bacterial motility, the expression of type three secretion system effector AvrPto, and the plant hypersensitive response triggered by strain DC3000. The results suggested that the extract from strain BR3 might offer an alternative method to control bacterial diseases in plants by targeting the GacS/GacA system.